Analisis Faktor-Faktor Yang Mempengaruhi Mahasiswa Dalam Menggunakan QRIS - Fajar, Ade; Salama, Hartini; Nurfahira, Muhammad Tegar; Suwarni, Indah (Asosiasi Dosen Peneliti Ilmu Keislaman dan Sosial, 2024)
College students are part of the community who have advantages in obtaining information and knowledge that is obtained easily and quickly compared to the general public, so that the use of QRIS can be used easily to meet student academic and other needs in daily activities. The purpose of this study was to analyze partially and simultaneously the factors that influence the interest of Ibnu Chaldun University students in using QRIS. This study uses descriptive quantitative methods. The population of this study were all students of Ibnu Chaldun University with 100 samples and data collection techniques using questionnaires in the form of google forms. This research is expected to be a reference for Bank Indonesia, and QRIS developers to continue to improve its quality so that it is in demand by the wider community. The results of this study indicate that Performance Expectancy, Social Environment and Habits have a positive and significant effect on student interest, especially at Ibn Chaldun University, and the most dominant factor is habit.